Customary sanctions in resolving violations of the "aluk todolo" of the Tana Toraja community - Suryamodjo, Pratama Yoland; Azisa, Nur; Haeranah, Haeranah (Jurnal Cakrawala Hukum, 2022)
Customary law must be able to protect and serve as a legal umbrella for indigenous peoples in terms of resolving customary violations committed by tourists, so this research is to determine the effectiveness of the application of customary sanctions in resolving violations of customary "Aluk Todolo" communities in Tana Toraja and North Toraja Regencies and observe the application of sanctions customary law in resolving violations of the "Aluk Todolo" custom which can provide a deterrent effect for violators and become the basis for legal protection for people in Tana Toraja Regency and North Toraja Regency who carry out this rule, using empirical research by collecting data based on observed facts obtained from the results of interviews and direct observation. The results of this study indicate that the application of customary sanctions in resolving violations of the traditional "Aluk Todolo" community in Tana Toraja Regency and North Toraja Regency is very effective in preventing customary violations and is the basis for legal protection for people in Tana Toraja Regency and North Toraja Regency who carry out the rules. How to cite item:Â Suryamodjo, P., Azisa, N., & Haeranah, H. (2022). Customary sanctions in resolving violations of the "aluk todolo" of the Tana Toraja community.Â Jurnal Cakrawala Hukum, 13(2), 214-223. DOI:https://doi.org/10.26905/idjch.v13i2.5655.